Conformational characterization of human eukaryotic initiation factor 2 alpha: a single tryptophan protein - Sreejith, R. K.; Yadav, Viveka Nand; Varshney, Nishant K.; Berwal, Sunil K.; Suresh, C. G.; Gaikwad, Sushama M.; Pal, Jayanta K. (Biochemical and Biophysical Research Communications, 2009)
The alpha-subunit of the human eukaryotic initiation factor 2 (heIF2 alpha), a GTP binding protein, plays a major role in the initiation of protein synthesis. During various cytoplasmic stresses, eIF2 alpha gets phosphorylated by eIF2 alpha-specific kinases resulting in inhibition of protein synthesis. The cloned and over expressed heIF2 alpha, a protein with a single tryptophan (trp) residue was examined for its conformational characteristics using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The steady-state fluorescence spectrum, fluorescence lifetimes (tau(1) = 1.13 ns and tau(2) = 4.74 ns) and solute quenching studies revealed the presence of trp conformers in hydrophobic and differential polar environment at any given time. Estimation of the alpha-helix and beta-sheet content showed: (i) more compact structure at pH 2.0, (ii) distorted alpha-helix and rearranged beta-sheet in presence of 4 M guanidine hydrochloride and (iii) retention of more than 50% ordered structure at 95 degrees C. Hydrophobic dye binding to the protein with loosened tertiary structure was observed at pH 2.0 indicating the existence of a molten globule-like structure. These observations indicate the inherent structural stability of the protein under various denaturing conditions. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Circular dichroism; heIF2 alpha; K562 cells; Molten globule; Steady-state and time-resolved fluorescence

Multistate unfolding of alpha-mannosidase from Canavalia ensiformis (Jack Bean): evidence for the thermostable molten globule - Kumar, Avinash; Gaikwad, Sushama M. (Biochemical and Biophysical Research Communications, 2010)
The relevance of partially ordered states of proteins (such as the molten-globule state) in cellular processes is beginning to be understood. We examined the conformational transitions in a multimeric and high molecular weight class II alpha-mannosidase from Canavalia ensiformis (Jack Bean) (Jb alpha-man) utilizing intrinsic fluorescence, solute quenching, hydrophobic dye binding, size exclusion chromatography and circular dichroism (CD) spectroscopy for the protein in presence of Guanidine hydrochloride (GdnHCl). The decomposition analysis of the protein spectra obtained during unfolding showed progressive appearance of class S, I, II and III trp. The parameter A and spectral center of mass showed multi state unfolding of the protein and phase diagram analysis revealed formation of an intermediate of Jb alpha-man in the vicinity of 1 M GdnHCl. The intermediate exhibited compact secondary and distorted tertiary structure with exposed hydrophobic amino acids on the surface, indicating the molten-globule nature. The dissociation, partial unfolding and aggregation of Jb alpha-man occurred simultaneously during chemical denaturation. The molten-globule possessed slightly higher hydrodynamic radius, perturbance in the structure up to 60 degrees C and stability of the structure up to 80 degrees C unlike the native Jack Bean alpha-mannosidase. The modes of chemical and thermal denaturation of the native protein were different. The solute quenching parameters confirmed the altered confirmation of the intermediate. Taken together, our results constitute one of the early reports of formation of GdnHCl induced molten globule in a class II alpha-mannosidase. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: alpha-Mannosidase; Circular dichroism; fluorescence; Guanidine hydrochloride; Molten globule; Thermostability; Unfolding

Conformational transitions in ariesaema curvatum lectin: characterization of an acid induced active molten globule - Sharma, Urvashi; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2011)
Biophysical characterization of a lectin from Ariesaema curvatum (ACL) was carried out using steady state as well as time resolved fluorescence and CD spectroscopy under various denaturing conditions. An intermediate with altered tryptophan microenvironment was detected in the phase diagram, which exibited pronounced secondary structure and hemagglutinating activity in presence of 0.25 M Gdn-HCl. An acid induced molten- globule like structure possessing activity and higher thermostability was detected. Transition to the molten globule state was reversible in nature. The lectin retained hemagglutinating activity even after incubation at 95 A degrees C. Both chemical and thermal unfolding of the lectin were found to consist of multistate processes. Fluorescence quenching of ACL was strong with acrylamide and KI. The single tryptophan was found to be surrounded by high density of the positively charged amino acid residues as shown by a ten fold higher K(sv) for KI compared to that for CsCl. The average lifetime of tryptophan fluorescence increased from 1.24 ns in the native state to 1.72 ns in the denatured state.
Keywords: Araceae; Fluorescence lifetime; Hemagglutinin; Molten globule; Secondary structure; Thermostability; Unfolding

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Conformational transitions of cinnamoyl CoA reductase 1 from leucaena leucocephala - Sonawane, Prashant D.; Khan, Bashir Mohammad; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2014)
Conformational transitions of cinnamoyl CoA reductase, a key regulatory enzyme in lignin biosynthesis, from Leucaena leucocephala (L1-CCRH1) were studied using fluorescence and circular dichroism spectroscopy. The native protein possesses four trp residues exposed on the surface and 66% of helical structure, undergoes rapid structural transitions at and above 45 C and starts forming aggregates at 55 C. LI-CCRH1 was transformed into acid induced (pH 2.0) molten globule like structure, exhibiting altered secondary structure, diminished tertiary structure and exposed hydrophobic residues. The molten globule like structure was examined for the thermal and chemical stability. The altered secondary structure of Ll -CCRH1 at pH 2.0 was stable up to 90 C. Also, in presence of 0.25 M guanidine hydrochloride (GdnHCI), it got transformed into different structure which was stable in the vicinity of 2 M GdnHCI (as compared to drastic loss of native structure in 2 M GdnHC1) as seen in far UV-CD spectra. The structural transition of LI-CCRH1 at pH 2.0 followed another transition after readjusting the pH to 8.0, forming a structure with hardly any similarity to that of native protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation Cinnamoyl CoA reductase; Conformation; Molten globule; Thermostability; Unfolding

Functional stability and structural transitions of kallikrein: spectroscopic and molecular dynamics studies - Dalal, Sayli; Mhashal, Anil; Kadoo, Narendra; Gaikwad, Sushama M. (Journal of Biomolecular Structure & Dynamics, 2017)
Kallikrein, a physiologically vital serine protease, was investigated for its functional and conformational transitions during chemical (organic solvents, Gdn-HCl), thermal, and pH induced denaturation using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The enzyme was exceptionally stable in isopropanol and ethanol showing 110% and 75% activity, respectively, after 96h, showed moderate tolerance in acetonitrile (45% activity after 72h) and much lower stability in methanol (40% activity after 24h) (all the solvents [90% v/v]). Far UV CD and fluorescence spectra indicated apparent reduction in compactness of KLKp structure in isopropanol system. MD simulation studies of the enzyme in isopropanol revealed (1) minimal deviation of the structure from native state (2) marginal increase in radius of gyration and solvent accessible surface area (SASA) of the protein and the active site, and (3) loss of density barrier at the active site possibly leading to increased accessibility of substrate to catalytic triad as compared to methanol and acetonitrile. Although kallikrein was structurally stable up to 90 degrees C as indicated by secondary structure monitoring, it was functionally stable only up to 45 degrees C, implicating thermolabile active site geometry. In GdnHCl [1.0M], 75% of the activity of KLKp was retained after incubation for 4h, indicating its denaturant tolerance. A molten globule-like structure of KLKp formed at pH 1.0 was more thermostable and exhibited interesting structural transitions in organic solvents. The above results provide deeper understanding of functional and structural stability of the serine proteases at molecular level.
Keywords: isopropanol tolerance; Kallikrein; MD Simulation; Molten globule; Serine protease; Thermostability

Investigation of structural and saccharide binding transitions of Bauhinia purpurea and Wisteria floribunda lectins - Agrawal, Sanskruthi B.; Ghosh, Deepanjan; Gaikwad, Sushama M. (Archives of Biochemistry and Biophysics, 2019)
Two novel medicinally important legume lectins from Bauhinia purpurea (BPL) and Wisteria floribunda (WFL) possessing extended sugar binding site were investigated for functional and conformational transitions using biochemical and biophysical techniques as well as bioinformatical tools. Homology model of BPL was constructed using the Schrodinger suite and docked with N-acetyl galactosamine and T-antigen disaccharide (Gal beta 1-3GalNAc alpha O-Me). The longer loop D in the structure of WFL compared to that in BPL was found to be responsible for its specificity to LacdiNac (beta-D-GalNAc-[1 -> 4]-DGlcNAc) over Gal beta 1-3GalNAc. BPL remained functionally stable up to 40 degrees C whereas WFL remained stable upto 70 degrees C indicating the strength of the sugar binding site geometry. Both the lectins showed intense but non-specific secondary structure in the range of 65-90 degrees C. WFL showed rapid aggregation above 80 degrees C as indicated by light scattering intensity. The lectins showed simultaneous dissociation and multistate unfolding in the vicinity of GdnHCl. At pH 1.0, both the lectins exhibited molten globule like structures, which were characterized further and were found to respond in a different way towards denaturants. The results have provided valuable insights into the molecular basis of the activity and stability of the two lectins.
Keywords: Conformation; Homology model; Lectin; Molten globule; saccharide binding; Thermal aggregation